The Influence Of Promotions And Service Quality On Customer Satisfaction At Assalaam Sukoharjo High School - Sari, Pertapa; Wiyadi, W; Soepatini, S (Ittishal Educational Research Journal, 2024)
This research aims to find out whether promotion and service quality have an influence on customer satisfaction at SMA Assalaam Sukoharjo. The research objects taken were 105 parents spread throughout Indonesia and data collection was carried out through questionnaires. The data analysis used is multiple linear regression. In this research, the results show that promotion and service quality have a positive and significant effect on customer satisfaction at SMA Assalaam Sukoharjo. Promotion has a positive and significant effect on customer satisfaction. This is proven by the calculated t value of 2.059 with a significance level of 0.042. This illustrates that the more and better promotions carried out by SMA Assalaam Sukoharjo, the higher the level of customer satisfaction. Service quality has a positive and significant effect on customer satisfaction. This is proven by the t count of 7.638 and a significance of 0.000. This illustrates that the higher and better the quality of service provided by SMA Assalaam Sukoharjo, the higher the level of customer satisfaction with that institution. It is hoped that these results can be an input for SMA Assalaam to always improve the quality of promotions and services provided to customers.